Brain MR Spectroscopy Changes Precede Frontotemporal Lobar Degeneration Phenoconversion in Mapt Mutation Carriers. Issue 5 (7th June 2019) - Chen, Qin; Boeve, Bradley F.; Tosakulwong, Nirubol; Lesnick, Timothy; Brushaber, Danielle; Dheel, Christina; Fields, Julie; Forsberg, Leah; Gavrilova, Ralitza; Gearhart, Debra; Haley, Dana; Gunter, Jeffrey L.; et al.
ABSTRACT: BACKGROUND AND PURPOSE: The objective of this study was to longitudinally investigate the trajectory of change in 1 H MRS measurements in asymptomatic MAPT mutation carriers who became symptomatic during follow‐up, and to determine the time at which the neurochemical alterations accelerated during disease progression. METHODS: We identified eight MAPT mutations carriers who transitioned from asymptomatic to symptomatic disease during follow‐up. All participants were longitudinally followed with an average of 7.75 years (range 4‐11 years) and underwent two or more single voxel 1 H MRS examinations from the posterior cingulate voxel, with a total of 60 examinations. The rate of longitudinal change for each metabolite was estimated using linear mixed models. A flex point model was used to estimate the flex time point of the change in slope. RESULTS: The decrease in the NAA/mI ratio accelerated 2.09 years prior to symptom onset, and continued to decline. A similar trajectory was observed in the presumed glial marker mI/Cr ratio accelerating 1.86 years prior to symptom onset. CONCLUSIONS: Our findings support the potential use of longitudinal 1 H MRS for monitoring the neurodegenerative progression in MAPT mutation carriers starting from the asymptomatic stage.